2012
DOI: 10.5897/ajfs12.039
|View full text |Cite
|
Sign up to set email alerts
|

The influence of fermentation and salting on the bacterial, chemical and sensory characteristics of catfish (Clarias buthupogon) based marinate in Nigeria

Abstract: Catfish (Clarias buthupogon) was treated with 10% w/w NaCl and 15% w/w NaCl with or without the addition of spices (1% w/w garlic powder and 1% w/w red pepper) and allowed to ferment naturally and at room temperature (28 ± 2°C) for two weeks. Bacte rial, chemical and sensory analyses were carried out on the unfermented non-salted and fermented salted samples of the fish species. Results obtained revealed that fermentation and salting caused a remarkable reduction in the total bacterial count from 2.29×10 6 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 4 publications
(9 reference statements)
1
2
0
Order By: Relevance
“…The high values of TVN measured in inoculated products were due to the activity of endogenous fish flora and to the proteolytic activities of the inoculated strains of S. xylosus as reported by Tremonte et al, 2010). The same trend of TVN content was reported during the fermentation of Clarias buthupogon for the production of fermented fish (Ezeama, 2012). This proteolytic activity was desirable for flavor development during the fermentation (Kaban & Kaya, 2009;Tremonte et al, 2010).…”
Section: Changes In Total Volatile Nitrogen (Tvn) During the Fermenta...supporting
confidence: 55%
See 2 more Smart Citations
“…The high values of TVN measured in inoculated products were due to the activity of endogenous fish flora and to the proteolytic activities of the inoculated strains of S. xylosus as reported by Tremonte et al, 2010). The same trend of TVN content was reported during the fermentation of Clarias buthupogon for the production of fermented fish (Ezeama, 2012). This proteolytic activity was desirable for flavor development during the fermentation (Kaban & Kaya, 2009;Tremonte et al, 2010).…”
Section: Changes In Total Volatile Nitrogen (Tvn) During the Fermenta...supporting
confidence: 55%
“…So, Enterobacteriaceae counts were significantly (p ˂ 0.05) reduced by the marinating process. Sallam (2008) and Ezeama (2012) reported that the use of citric acid, salt and spices have bacteriostatic and bactericide effects on the flora.…”
Section: Effect Of the Marinating On The Fish Fleshmentioning
confidence: 99%
See 1 more Smart Citation